# Simplify the expression first and then substitute 2 for x. 9x+6+4x+5=?

### 8 Answers

Relevance

- 2 months ago
9x+6+4x+5

1. Group like terms

(9x+4x) + (6+5)13x+11

2. Substitute 2 for x => 13*2+11

3. Work out

26+11=37

- 2 months ago
you do 9x + 4x which is 13x, because 9+4=13

Then you add the 6 and 5 together so, 6+5=11

finally add the two terms together so 13x+11

If you want to work out when x=2 you multiply

13 by 2 because of the 3x so 13*2=26

then add the 26 to the 11 so, 26+11

= 37 this is your answer

- How do you think about the answers? You can sign in to vote the answer.
- Ms. WorthLv 72 months ago
9x + 6 + 4x + 5

1) Simplify by combining like terms

After you combine 9x with 4x, and the 6 with the 5, you get this:

13x + 11 <-- simplified

2) Sub in 2 in the place of x

13(2) + 11

3) Evaluate the expression for "x equals 2"

26 + 11

37 <-- evaluated for "x equals 2"

- 2 months ago
9x+6+4x+5 = 9x+4x+11 = x(9+4)+11 = x(13)+11 = 13x+11

?=13(2)+11=37

thus the unknown variable = 37

Still have questions? Get your answers by asking now.